Hak Kepemilikan Perumahan Di Atas Bangunan Gedung Komersil - Pangerang, Cut Hardiyanti; Nur, Sri Susyanti; Arisaputra, Muhammad Ilham (Batulis Civil Law Review, 2021)
This research aims to find the regulation regarding to the spatial utilization above a commercial building for housing and to examine ownership rights for housing built on top of the building. This research is an empirical legal research with research locations in DKI Jakarta, precisely at the Cosmo Park and The Villas. The research location was considered in DKI Jakarta because the existence of housing above commercial buildings in Indonesia was only in DKI Jakarta. The speakers in this research were the Head of Planning and Utilization of City Spaces at the department of copyright works, spatial planning, and land in DKI Jakarta province (DCKTRP), Building Supervision Staff at the DCKTRP DKI Jakarta province and the Directorate General of Spatial Planning at the Ministry of Agrarian Affairs and Spatial Planning / National Land Agency. The results of this research indicate that the current regulation regarding the spatial utilization above commercial buildings for housing refers to the local RTRW and RDTR whose spatial utilization allocations must be in accordance with the stipulated permits. Permits are granted in the form of location permits, space utilization permits and building construction permits in accordance with applicable local scale regulations. For the Cosmo Park and The Villas housing in DKI Jakarta, there is a mismatch between the initial IMB and the current use of the building. So the important thing that must be considered in the future construction of housing on commercial buildings is that the presentation of the IMB must be in accordance with the current construction realization. Ownership rights for housing built on top of the building, namely the property rights for flat units (strata title). Strata title refers to individual ownership of a proportionally part of a building either horizontally or vertically.